Mobilizing women voters in Pakistan - Chaudhry, Zain (PEGNet policy brief, 2020)
In most developing countries, politicians are mostly male, whose politics revolves around male household heads. The system does not stop women from voting, but politicians do not campaign directly for the female vote. A campaign run by a politician in Pakistan focusing only on women increased his vote share by 3.6 percentage points (in an election where he lost by 0.08 percent). The campaign had a much larger effect when information was given to women alone and not alongside men.